Applicability of protease and urea as a molluscicide for Pomacea canaliculata (Siput Gondang Emas) - Noor Hasyierah, Mohd Salleh (Universiti Malaysia Perlis (UniMAP), 2019)
Pomacea canaliculata is regarded as one of the most destructive molluscs as it causes severe damage to paddy fields. This mollusc is commonly combated by using chemical molluscicide like metaldehyde, which is known as toxic chemicals, therefore causes negative impact to the farmers and the environment. Hence, there is a great demand for a user and environmental-friendly molluscicide to reduce P. canaliculata population. The present study investigates the applicability of protease and urea as an alternative molluscicide for combating both flesh and eggs of P. canaliculata. Studies on the effect of each agent on snail eggs cover chemical and physical analyses; namely unhatchability, cuticle protein profile, water loss, conductivity, gas exchange and morphological changes. For snail flesh, it covers biological, chemical and physical studies, namely, mortality, respiration, food intake, responsiveness, movement, protein, ammonia and peroxidase level of the flesh. The studies were extended by producing cell free extract protease (CFE protease) using locally available raw material like cassava, and subsequently applied as a biomolluscicide. Likewise, studies regarding urea were also extended by using coated urea with rice husk ash and starch before subsequently applied to the paddy demonstration plot. For the flesh of P. canaliculata studies, it was found that the mortality were 31% and 90% after exposure to 3.9U/mL CFE protease and 0.02M urea respectively for 20hrs. It was also observed that the respiration rate increased proportionally with the increase of urea concentration. Additionally, the exposure to CFE protease and urea also reduced the snail appetite, responsiveness and movement as compared to the control snail. Extension of the work using coated urea for paddy plot studies saved 93% of paddy from snail attack. As for the P. canaliculata eggs studies, 71%, 52% and 35% hatchability have been suppressed after treating to 0.75U/mL commercial protease, 0.19U/mL CFE protease and 0.02M urea respectively. Besides that, the rate of conductivity, water loss and respiration increased proportionally with the increase of either commercial protease activity or urea concentration. The findings from these studies show the applicability of protease and urea as a molluscicide for both the flesh and eggs of P. canaliculata.